POLICY IMPLEMENTATION AND IMPLICATIONS OF WATER TARIFF AND CUSTOMER CONNECTION FEE ADJUSTMENTS IN BANGGAI REGENCY - Sahraen Sibay; Slamet Riadi; Muh Nawawi; Haniyatul Husna Md Mohtar (Universitas Lampung, 2025)
This study analyzes the implementation of the policy on adjusting drinking water tariffs and new customer connection fees at the Regional Drinking Water Company (PERUMDAM) of Banggai Regency, based on Director’s Decision No. 01/PERUMDAM-BGI/VI/2021. Using a descriptive qualitative approach and integrating theories of policy implementation, administrative law, economic regulation, and constitutional principles on the right to water, the research finds that implementation remains suboptimal. Communication is generally effective, but employees often fail to perform their roles professionally. Resource limitations, including inadequate technical equipment and inaccurate distribution maps, persist despite available funding. While disposition and bureaucratic structures are formally adequate, leadership lacks commitment to assigning tasks based on competence and enforcing decisions consistently. These shortcomings highlight the need for a new implementation model that integrates administrative, economic, environmental, and constitutional legal frameworks with good governance principles to balance operational sustainability and the community’s right to affordable water access.